MENTAL PERSONALITY DISORDERS: CURRENT STATE OF THE PROBLEM STATEMENT (Psychology Travelogs, 2023)
The development of personality depends on physiological, psychological, and social changes that occur throughout a person's life. Genetic factors can also increase the risk of developing mental illnesses, but upbringing and experience also play an important role in shaping personality and can reduce this risk. However, hereditary factors are not always decisive, as their transmission is random.The aim of the research was to determine the features of external driving factors that lead to the development of destructive formations in the mental activity of the individual, as well as to identify internal determinants that provoke disturbances in the behavioral and cognitive-emotional spheres of a person.The theoretical-methodological approach refers to the specific approach or methodology used to study a particular phenomenon or problem. In this case, the approach was based on qualitative methods of analytical research. This type of research involves gathering data through methods such as interviews, observations, and document analysis, and analyzing it inductively to identify patterns and themes.The research presents data that reflect the current state of the problem of mental disorders of personality in the world, describe their etiology, and highlight effective approaches to combating them. The initial hypothesis was confirmed during the experiment, and after studying world practices in this field, a practical model for restoring mental health was developed. In further research, it will be possible to focus on the analysis of psychocorrectional programs and the study of pharmacological components for the treatment of personality mental disorders.The results of the scientific research are significant for professionals in the psychological field, as well as for educators and social organizations for a comprehensive understanding of the issue.
Keywords: self-regulation; behavioral disorders; emotional imbalance; therapy; drug treatment